1786 Mass. Acts 87, ch. 38 - (:unkn) unknown (General Publisher, 1786)
Prohibited being armed with clubs or other weapons while in a group of twelve or more and "unlawfully, routously, riotously, or tumutluously assembled."
--
Keywords: CARRY - INTENT TO COMMIT CRIME